Market quality and structural changes in the trading system. The case of X-Stream on the Colombian stock exchange (2014)
Purpose. The purpose of this paper is to study the effect of X‐Stream, the new trading platform of the Colombian Stock Exchange since February 2009, on the market quality. Design/methodology/approach. The authors test the effect of X‐Stream on market quality variables, such as liquidity (bid‐ask spread and price impact), daily and intraday volatility and trading activity, using mean tests, panel data and conditional variance models. The authors use a proprietary database of transactions and orders from the exchange. Findings. The evidence suggests that X‐Stream improved the liquidity and trading activity and reduced the volatility of the overall market, especially of the most liquid stocks. Practical implications. These results support the investment on more sophisticated trading systems in emerging markets. Originality/value. Contributing to the literature on market quality, this paper provides novel evidence of the effect of reforms on market design, trading rules and operational capabilities on a small and low‐liquidity emerging stock market.